Photodegradation of an Herbicide (2-methyl-4-chlorophenoxyacetic acid) in the Presence of “TiO[2], SnO[2], SnO[2]/TiO[2] Nanoparticles – Polypropylene Fibrous Carrier” Systems - Lysak I. A. Ilya Aleksandrovich; Malinovskaya T. D. Tatyana; Tchaikovskaya O. N. Olga; Artyushin V. R. Vyacheslav (2015, 2015)
Title screen